Analysis of Drug Logistics Management in the Pharmacy Installation of Klaten District Health Office - Listyorini Wulandari; Indasah Indasah; Byba Melda Suhita (Journal for Quality in Public Health, 2020)
Drug is an element supproting the health care system. Logistics management start from the planning process, procurement, storage, distribution, recording and reporting drugs. The purpose of the research was to explore drug logistic management at the pharmacy installation in the working area of Klaten District Health Office. Research design uses descriptive qualitative research. Data collection used indepth interview techniques with a total sample are 12 informants. From the results of the research it was found that drug planning at the health center pharmacy installation was carried out by the drug manager himself or in a team with the assistant pharmacist or treasurer of the health center. The drug needs planning process in the health center is carried out by recapitulating reports from the health center and the other units in the Usage Sheet and the Drug Request Sheet (LPLPO). Drug planning is carried out every month. Drug procurement is carried out by the consumption method and carried out through e-catalog once a year with buffer stock of one and a half years. The drug storage layout is accordance with provisions, safeguarding the quality of the drug by placing drugs on the pallet and shelves but there is no temperature measurement. Examination of drugs that come, drugs needed by the health center and drug distribution have been carried out according to the procedure. The recording and reporting of drugs in the health center uses sympus whereas in other units manually using LPLPO